Cancer-associated thoracic aorta arterial thrombosis: case report and review of the literature - Miguel Borregón; María Valero; Asia Ferrández; Álvaro Muñoz; Carmen Roque; Javier-David Benítez-Fuentes (Frontiers in Cardiovascular Medicine)
BackgroundArterial thrombosis is an uncommon complication in cancer patients, often overshadowed by venous thromboembolic events. Its occurrence in patients with solid tumors on active antineoplastic treatment poses a significant clinical challenge.Key clinical questionGiven the lack of consensus on the optimal therapy for arterial thrombosis in cancer patients, the best practices for managing an aortic thrombus, and the benefit of low molecular weight heparin (LMWH) must be reviewed.Clinical approachWe present the case of a 70-year-old female with stage IVA lung adenocarcinoma who developed an aortic thrombus during chemo-immunotherapy. The thrombus was successfully treated with LMWH, avoiding further complications, and allowing for the continuation of her cancer therapy.ConclusionsThis case highlights the importance of early detection and management of arterial thrombus in cancer patients. LMWH proved effective in resolving the thrombus, underscoring its role in managing such complications.